Indústria informal de confecções e mercado de trabalho : um estudo sobre a Grande Natal (1977-2003) - Oliveira, Ivanillton Passos de (2004)
The process of globalization which has characterized today s Brazilian economic development is determining in the restructuring of productive capital, influencing the development of an economic model, founded on greater competition and use of technology. As a consequence of that, there has been a certain disorganization of the economy, the growth of social inequalities and the lack of structuring of the labor market and the social security system. This has favored a rapid growth of the urban informal economy in Brazil. In Rio Grande do Norte state, the Greater Natal area is the main production center. This is where this study found 58 informal textile industries. In the research, the organizational structure of these industries, characterized by intensive use of labor vis-à-vis the use of capital, problems with putting production in the market place, although links with the formal sector were evident, is analysed. The research also focuses on the relationship labor x capital, the nature and volume of the industrial activity in the 58 industries, their proprietors and 120 employees